2013
DOI: 10.1124/jpet.113.203299
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Wee1 in the Circadian Rhythm–Dependent Intestinal Damage Induced by Docetaxel

Abstract: Docetaxel, a semisynthetic taxane, is effective for the treatment of some solid cancers; however, docetaxel-induced intestinal damage leads to poor prognosis in some patients. Although such adverse effects have been reported to depend on the dosing-time of docetaxel, the mechanisms involved remain unclear. Wee1 expression is controlled by the clock gene complex, clock/bmal1, and contributes to cell-cycle progression. The present study was undertaken to evaluate the potential role of Wee1 in the circadian rhyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…This hypothesis is supported by recent data that overexpression of Wee1 is commonly found in cisplatin-resistant carcinoma cells [34]. Likewise, docetaxel has been shown to increase Wee1 expression in rat intestinal mucosa [35]. A number of in vitro as well as in vivo studies have demonstrated a synergistic treatment response when Wee1 inhibition is combined with DNA-damaging agents, including, recently, in malignant mesothelioma [36], a cancer which affects the serosal cavities and shares morphological, immunohistochemical and genetic characteristics with serous OC [17].…”
Section: Discussionsupporting
confidence: 67%
“…This hypothesis is supported by recent data that overexpression of Wee1 is commonly found in cisplatin-resistant carcinoma cells [34]. Likewise, docetaxel has been shown to increase Wee1 expression in rat intestinal mucosa [35]. A number of in vitro as well as in vivo studies have demonstrated a synergistic treatment response when Wee1 inhibition is combined with DNA-damaging agents, including, recently, in malignant mesothelioma [36], a cancer which affects the serosal cavities and shares morphological, immunohistochemical and genetic characteristics with serous OC [17].…”
Section: Discussionsupporting
confidence: 67%
“…Several clock genes act as gatekeepers in the cell cycle (Matsuo et al , 2003). BMAL1/CLOCK controls the cell cycle by directly regulating the expression of WEE1, an inhibitor of CDC2/cyclin B1 (Obi‐Ioka et al , 2013; Farshadi et al , 2019). PER1 inhibits cyclin D1 (Fu et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several clock genes act as gatekeepers in the cell cycle (Matsuo et al , 2003). BMAL1/CLOCK controls the cell cycle by directly regulating the expression of WEE1, an inhibitor of CDC2/cyclin B1 (Farshadi et al , 2019; Obi-Ioka et al , 2013). PER1 inhibits Cyclin D1 (Fu et al , 2016).…”
Section: Discussionmentioning
confidence: 99%